Cultural Orientation of Self-Bias in Perceptual Matching - Jiang, Mengyin; Wong, Shirley K. M.; Chung, Harry K. S.; Sun, Yang; Hsiao, Janet H.; Sui, Jie; Humphreys, Glyn W. (Frontiers in Psychology, 2019)
Previous research on cross-culture comparisons found that Western cultures tend to value independence and the self is construed as an autonomous individual, while Eastern cultures value interdependence and self-identity is perceived as embedded among friends and family members. The present experiment explored these cultural differences in the context of a paradigm developed by Sui, He and Humphreys, which found a bias towards the processing of self-relevant information using perceptual matching tasks. In this task, each neutral shape (i.e. triangle, circle, square) is associated with a person (i.e. self, friend, stranger), and faster and more accurate responses were found to formerly neutral stimuli tagged to the self compared to stimuli tagged to non-self. With this paradigm, the current study examined cross-cultural differences in the self bias effect between participants from Hong Kong and the United Kingdom. Results demonstrated a reliable self-bias effect across groups consistent with previous studies. Importantly, a variation was identified in a larger self-bias towards stranger-associated stimuli in the United Kingdom participants than the Hong Kong participants. This suggested the cultural modulation of the self bias effect in perceptual matching.